Copper/reduced graphene oxide film modified electrode for non-enzymatic glucose sensing application - Phetsang, Sopit (Sci Rep, 2021)
Numerous studies suggest that modification with functional nanomaterials can enhance the electrode electrocatalytic activity, sensitivity, and selectivity of the electrochemical sensors. Here, a highly sensitive and cost-effective disposable non-enzymatic glucose sensor based on copper(II)/reduced graphene oxide modified screen-printed carbon electrode is demonstrated. Facile fabrication of the developed sensing electrodes is carried out by the adsorption of copper(II) onto graphene oxide modified electrode, then following the electrochemical reduction. The proposed sensor illustrates good electrocatalytic activity toward glucose oxidation with a wide linear detection range from 0.10 mM to 12.5 mM, low detection limit of 65 µM, and high sensitivity of 172 μA mM(–1) cm(–2) along with satisfactory anti-interference ability, reproducibility, stability, and the acceptable recoveries for the detection of glucose in a human serum sample (95.6–106.4%). The copper(II)/reduced graphene oxide based sensor with the superior performances is a great potential for the quantitation of glucose in real samples.